Characteristics of Tallow-Based Soap by the Addition of Kefir Curd from Goat Milk - Dina Tri Marya; Anjar Sofiana; Muhammad Hanif (Faculty of Animal Science, Universitas Brawijaya, 2023)
Tallow is a less economical and underutilized animal's fat. In fact, tallow comprises triglycerides from several fatty acids which support skin protection by increasing moisture and preventing dryness. The use of tallow in soap manufacturing will gain its interest and enhance its value added. In this study, solid soaps are prepared using tallow as raw materials by adding kefir curd from goat milk. This study analyzed the physicochemical and organoleptic characteristics of the particular soaps by developing a completely randomized design (CRD) experiment. The kefir curd gradually increased its proportion in soap manufacturing and observed its effect on pH, moisture content, degree of foaming, and foam stability. Organoleptic tests for both hedonics and hedonic qualities were also performed and analyzed by Kruskal Wallis's nonparametric analysis. The statistical analysis reported a significant difference of 6% curd addition on pH (p<0.05) than fewer or without curd additions. The average moisture content of soap with a 6% curd addition did not differ significantly from the soap with a 4% curd addition. However, these moisture contents significantly differed from others by less or without curd addition. All soap formulations also showed no significant difference in foam height and stability. Meanwhile, the hedonic quality tests showed that the soaps has moderate foam forming degree and less fat aroma. In addition, the foam forming degree and fat aroma was not significant for all formula. The hedonic test showed that the panelists preferred tallow soap with a 6% curd addition, even though the analysis reported no significantly different (p>0.05).